2021
DOI: 10.1021/acsami.1c07611
|View full text |Cite
|
Sign up to set email alerts
|

Linking Perfluorosulfonic Acid Ionomer Chemistry and High-Current Density Performance in Fuel-Cell Electrodes

Abstract: Transport phenomena are key in controlling performance of electrochemical energy-conversion technologies and can be highly complex involving multiple length-scales and materials/phases.Material designs optimized for one reactant species transport however may inhibit other transport processes. We explore such trade-offs in the context of polymer-electrolyte fuel-cell (PEFC) electrodes, where ionomer thin films provide the necessary proton conductivity but retard oxygen transport to the Pt reaction site and caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 62 publications
0
40
0
Order By: Relevance
“…The novel ionomer should have higher gas permeability and decent proton conductivity at low humidity but simultaneously should not have a too high interfacial resistance to the catalyst, which can be accounted to, for instance, the high anion concentration. [ 9 ] Requirements and targets for fuel cells and electrolyzers are discussed in the following sections.…”
Section: Challenges and Perspectives For Next‐generation Measmentioning
confidence: 99%
See 1 more Smart Citation
“…The novel ionomer should have higher gas permeability and decent proton conductivity at low humidity but simultaneously should not have a too high interfacial resistance to the catalyst, which can be accounted to, for instance, the high anion concentration. [ 9 ] Requirements and targets for fuel cells and electrolyzers are discussed in the following sections.…”
Section: Challenges and Perspectives For Next‐generation Measmentioning
confidence: 99%
“…To achieve these very ambitious goals, some "early stage" materials were combined to estimate a polarization curve (dashed green line) that theoretically can exceed the 2030 target value (solid green line). Those materials include increased catalytic active sites and intrinsic activity [5,6] and catalyst layers with mesoporous Pt/C from GM R&D. [7] The optimal electrode ionomer should provide high proton conductivity at high temperatures (>100 °C) and low humidity (<50% relative humidity (RH)), thus high ion exchange capacity (IEC) [8] without poisoning the catalyst [9,10] and finally a high oxygen permeability. [11,12] The gas diffusion layers should also be improved to significantly reduce the gas transport losses.…”
Section: Introductionmentioning
confidence: 99%
“…In sub-micrometer-thick films of conventional ionomers (such as Nafion), the phase segregation and ionic domain connectivity are sacrificed due to dimensional and interfacial constraints. , These cause a decrease in the size of ion-conducting domains to ∼1.5–2 nm in sub-micrometer-thick, hydrated Nafion films from ∼4 nm in corresponding bulk membranes . Based on the current understanding of ionomers, a common school of thought is that ion channels with a narrow diameter (≤2 nm) cause nanoconfinement effects on flow and negatively impact the proton conductivity. , However, the trends in proton conduction through narrow (1–2 nm) versus very narrow (sub-nanometer) ion channels are very thought-provoking .…”
Section: Introductionmentioning
confidence: 99%
“…6,9,12,13 However, it has been reported that the ultrathin coating of the ionomer introduces an O 2 permeation barrier to catalyst particles within the primary pores and on the surface of the secondary pore structure, a primary factor in the added mass transport resistances that cannot be explained by the agglomerate model alone. 14 As a result, there has been intense research effort in understanding the O 2 permeation through thin ionomer films, 15−17 the effect of the chemical nature of the ionomer, 14,18 the impact of porosity of the support, 19 and the influence of catalyst ink composition on mass transport limitations within the CL. 20,21 Despite intense research surrounding PFSA ionomers, there are growing concerns over the use of potentially hazardous chemical feedstocks, and the complex synthesis results in only a handful of chemical manufacturing companies having the capability to produce them, adding to the expense of PFSAs.…”
mentioning
confidence: 99%
“…These are critical in facilitating the diffusion of gases within and the removal of water from the CL, as described by agglomerate models. , Polyelectrolytes, such as the typically used perfluorosolfonic acid (PFSA) ionomer Nafion, are also included in the ink dispersion to encapsulate and bind the Pt/C agglomerates, providing proton conductive pathways throughout the entire CL. ,,, However, it has been reported that the ultrathin coating of the ionomer introduces an O 2 permeation barrier to catalyst particles within the primary pores and on the surface of the secondary pore structure, a primary factor in the added mass transport resistances that cannot be explained by the agglomerate model alone . As a result, there has been intense research effort in understanding the O 2 permeation through thin ionomer films, the effect of the chemical nature of the ionomer, , the impact of porosity of the support, and the influence of catalyst ink composition on mass transport limitations within the CL. , …”
mentioning
confidence: 99%